Social Construction of Tourist in Choosing The Ullen Sentalu Museum as A Tourism Destination: - - Septadinusastra, Vina Alvinia; Kurnia Sari, Rizkita (JURNAL KOMUNIKATIO, 2024)
Yogyakarta as one of the preferred tourism destinations for domestic and foreign tourist. Tourist destination that prioritize on culture and history, creates its own charmed for tourist. One of the tourism destination brands in Yogyakarta is The Ullen Sentalu Museum, which offers a different and unique concept from other museums. Ullen Sentalu museum building had European architecture, all museum collection come from the first hand, there are educators guiding the tourist. The purpose of this study was to determine the social construction of tourist in choosing the Ullen Sentalu Museum as a tourist destination who travel frequently and active users of social media. The research method used was qualitative method with a case study approach. The result of this study were: (1) Tourist chosen the Ullen Sentalu Museum as their destination through word of mouth, (2) Social Media is used to provide testimonials to tourist who did not know or had never visited the Ullen Sentalu Museum, (3) The existence of educators in telling history by storytelling is a supporting factor that attracts tourists to come back again to Ullen Sentalu Museum.